IEEE 1451.1 Standard and XML Web Services: a Powerful Combination to Build Distributed Measurement and Control Systems - Viegas, Vítor (2006)
In 2005, we presented the NCAP/XML, a prototype of NCAP (Network Capable Application Processor) that runs under the .NET Framework and makes available its functionality through a set of Web Services using XML (eXtended Markup Language). Giving continuity to this project, it is time to explain how to use the NCAP/XML to build a Distributed Measurement and Control System (DMCS) compliant with the 1451.1 Std. This paper is divided in two main parts: in the first part, we present the new software architecture of NCAP/XML (which suffered some changes since the first version), and secondly, we describe the network configuration of a Web-enabled DMCS, which includes several NCAP/XML stations, a database and a Web Server.